A conceptual model for migratory tundra caribou to explain and predict why shifts in spatial fidelity of breeding cows to their calving grounds are infrequent - Gunn, Anne; Poole, Kim G.; Nishi, John S. (Rangifer, 2012)
Calving grounds of migratory tundra caribou (Rangifer tarandus) have two prominent characteristics. Firstly, the cows are gregarious, and secondly, the annual calving grounds spatially overlap in consecutive years (spatial fidelity). The location of consecutive annual calving grounds can gradually shift (either rotationally or un-directional) or more rarely, abruptly (non-overlapping). We propose a mechanism to interpret and predict changes in spatial fidelity. We propose that fidelity is linked to gregariousness with its advantages for individual fitness (positive density-dependence). Our argument is based on a curvilinear relationship between the density of cows on the calving ground (which we use to index gregariousness) and spatial fidelity. Extremely high or low densities are two different mechanisms which can lead to reduced spatial fidelity to annual calving grounds and reflect the caribou’s adaptive use of its calving ranges.